Laboured reading and musculoskeletal pain in school children - the role of lifestyle behaviour and eye wear: a cross-sectional study - Hanne-Mari Schiøtz Thorud; Randi Mork; Cecilie Onshuus Bjørset; Stuart J. Gilson; Lene A. Hagen; Trine Langaas; Hilde R. Pedersen; Ellen Svarverud; Gro Horgen Vikesdal; Rigmor C. Baraas (BMC, 2022)
Abstract Background Lifestyle behaviour in children and adolescents has become increasingly sedentary and occupied with digital work. Concurrently, there has been an increase in the prevalence of headache, neck- and low back pain, which are leading causes of disability globally. Extensive near work and use of digital devices are demanding for both the visual system and the upper body head-stabilizing musculature. Uncorrected vision problems are present in up to 40% of Nordic school children, and a lack of corrective eye wear may cause eyestrain, musculoskeletal pain and headache. The aim of this study was to investigate associations between laboured reading, musculoskeletal pain, uncorrected vision, and lifestyle behaviours in children and adolescents. Methods This was a cross-sectional study with a total of 192 Norwegian school children aged 10-11 and 15-16 years. As a part of a school vision testing program, the children completed an online questionnaire about general and ocular health, socioeconomic status, academic ambition, near work and related symptoms, upper body musculoskeletal pain, and physical and outdoor activities. Results The 15-16-year-olds had a more indoor, sedentary, digital-based lifestyle with higher academic demands, compared with the 10-11-year-olds. Concurrently, reading became more laboured and upper body musculoskeletal pain increased with age. Girls reported more symptoms, higher academic ambitions, and more time spent on schoolwork and reading, compared with boys. Non-compliance in wearing prescribed eye wear (glasses or contact lenses), increased use of near digital devices, and experiencing visual stress (glare) were positively associated with laboured reading and upper body musculoskeletal pain. Conclusions A screen-based lifestyle with high academic demands challenges the ability to sustain long hours of static, intensive near work. Extensive near work tires the visual system and upper body musculature and provokes laboured reading and musculoskeletal pain symptoms. This study emphasizes the importance of regular eye examinations in school children, and the need to raise awareness among children, parents, and school- and health personnel about the importance of optimal vision and visual environment for academic performance and health.